Disartria hipocinética na Doença de Parkinson: correlação entre avaliação clínica, análise acústica e percepção subjetiva - Sara Alois de Abreu Martins da Costa (2023)
We know that dysarthria has a high prevalence in individuals diagnosed with Parkinson's disease, impacting their communication. Through the understanding of the disorders caused by dysarthria, communicative strategies can be created to adapt the treatment process and quality of life of individuals with the diagnosis. This study aims to compare the performance of individuals with Parkinson's Disease and a control group in a diadochokinetic test to understand hypokinetic dysarthria. In addition, the impact of the disease on clinical assessments of motor and orofacial impairment and the subjective conditions informed in self-questionnaires were verified to understand better the effect on communication and quality of life of individuals diagnosed with PD. As a result, we found a homogeneous group regarding gender, age, and education. Impairments in the clinical motor assessment impact the phonation rate (PhR), reducing the phonation rate as the patient presents more relevant motor impacts. Another relevant information in the study was the impact of age on mean syllable duration (ASD) values and FDA-2 results. Among the self-questionnaires used, we found that the TMF and PhR are negatively related to the Beck and PDQ-39. In conclusion, worsening motor alterations and poor self-questionnaire results impact speech production, mainly in DDK and TMF tasks.